Organic magnetic composite material, preparation method and application thereof
By grafting nanocarbon materials with magnetic phthalocyanine through covalent bonds in organic magnetic composites, the problems of uneven dispersion of nanocarbon materials and insoluble metal phthalocyanines are solved, and high temperature resistance, low density and strong absorption are prepared. Properties of organic magnetic composite materials meet the needs of high-tech fields such as aerospace.
Patent Information
- Application Number
- CN201911154495.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-11-22
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2039-11-22
AI Technical Summary
The existing organic magnetic composite materials have unstable performance at high temperatures, the nanocarbon materials are unevenly dispersed, and metal phthalocyanines are difficult to dissolve, making it difficult to meet the needs of high-temperature resistance, low density, wide absorption, etc. in high-tech fields such as aerospace.
By reacting nanocarbon materials, biphenyl compounds and 4-nitrophthalene in an organic solvent, nanocarbon materials/phthalene monomers are generated and reacted with magnetic metal salts to form magnetic phthalocyanines Metal prepolymers are obtained by covalent bond grafting, which solves the problems of uneven dispersion of nanocarbon materials and insoluble metal phthalocyanine.
The prepared organic magnetic composite materials have excellent properties of high temperature, low density, strong absorption, low frequency, high strength and high modulus, and are suitable for wave absorbing materials in high-tech fields.
Smart Images

Figure CN112837918B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of wave absorbing materials, and in particular to an organic magnetic composite material, a preparation method thereof and an application thereof. Background Art
[0002] Magnetic materials are widely used in the field of absorbing materials. Traditional inorganic magnetic materials have poor processing performance, easy oxidation, and high specific gravity, which limits their application in high-tech and cutting-edge fields. Organic magnetic materials are gradually gaining attention due to their flexible processing characteristics, good chemical resistance, and relatively stable magnetic properties.
[0003] Organic magnetic materials are mainly divided into structural and composite types. The structural type is a polymer with strong magnetism itself, while the composite type is a composite of a polymer matrix and an inorganic magnetic powder. However, the dispersibility and interfacial bonding strength of the inorganic magnetic powder in the polymer matrix are poor. Therefore, the processing performance and some functionality of the composite type are far weaker than those of structural organic magnetic materials.
[0004] With the rapid development of high-tech industries such as aerospace, electronic information, etc., the requirements for materials are becoming more and more stringent, such as high temperature resistance, low density and wide absorption, so it is necessary to develop a wave-absorbing material that is both resistant to high temperatures and has strong magnetism. In addition to the advantages of high temperature resistance, high strength and high modulus, phthalocyanine polymers can also coordinate with metal ions to form compounds with the properties of metal ions; therefore, magnetic polymers such as iron phthalocyanine, cobalt phthalocyanine, and nickel phthalocyanine have received widespread attention. At present, a single magnetic loss mechanism can no longer meet the current "thin, light, wide, and strong" requirements of wave-absorbing materials. It is necessary to combine carbon materials with magnetic materials to prepare composite materials with multiple loss mechanisms. However, since nanocarbon materials are easy to agglomerate and difficult to disperse, magnetic polymers such as iron phthalocyanine have low solubility in organic solvents and are very easy to aggregate, which limits their application. Summary of the invention
[0005] The technical problem solved by the present invention is to provide a method for preparing an organic magnetic composite material. The organic magnetic composite material prepared in the present application solves the difficult problems of poor solubility of metal phthalocyanine and uneven dispersion of nano-carbon materials, so that the organic magnetic-based absorbing material has excellent properties of high temperature resistance, low density, strong absorption, low frequency, high strength and high modulus.
[0006] In view of this, the present application provides a method for preparing an organic magnetic composite material, comprising the following steps:
[0007] A) reacting a nano-carbon material, a catalyst, a biphenyl compound and 4-nitrophthalonitrile in an organic solvent to obtain a nano-carbon material / phthalonitrile monomer; the biphenyl compound is a biphenyl compound containing a hydroxyl substituent;
[0008] B) reacting the nano-carbon material / phthalonitrile monomer and a magnetic metal salt in a solvent to obtain a magnetic phthalocyanine metal prepolymer;
[0009] C) curing the magnetic phthalocyanine metal prepolymer or its composition to obtain an organic magnetic composite material.
[0010] Preferably, the biphenyl compound is 4,4'-dihydroxybiphenyl, the nanocarbon material is one or more of carbon nanotubes with soluble functional groups and graphene oxide; the magnetic metal salt is one or more of magnetic salts of iron, cobalt and nickel.
[0011] Preferably, step A) is specifically:
[0012] The nano-carbon material and 4,4'-dihydroxybiphenyl are reacted in a strong polar organic solvent, and then 4-nitrophthalonitrile and anhydrous potassium carbonate are added to obtain a nano-carbon material / phthalonitrile monomer after the reaction.
[0013] Preferably, the mass ratio of the nano-carbon material, 4,4'-dihydroxybiphenyl, 4-nitrophthalonitrile and anhydrous potassium carbonate is 1:(10-20):(20-40):(5-10).
[0014] Preferably, the mass ratio of the nano-carbon material / phthalonitrile monomer and the magnetic metal salt is (10-20):1.
[0015] Preferably, the curing includes pre-curing and post-curing performed sequentially; the pre-curing is specifically maintained at 200°C for 2 hours and then maintained at 250°C for 4 hours, and the post-curing is specifically maintained at 300°C for 4 hours and then maintained at 350°C for 4 hours.
[0016] Preferably, step B) is specifically:
[0017] The nano-carbon material / phthalonitrile monomer is mixed with a strong polar solvent, heated and then a magnetic metal salt is added, and the mixture is dried after reaction to obtain a magnetic phthalocyanine metal prepolymer.
[0018] Preferably, the heating temperature is 60-90°C, the reaction temperature is 160-180°C, the reaction time is 2-8 hours, and the drying temperature is 60-80°C.
[0019] The present application also provides an organic magnetic composite material prepared by the preparation method, which is obtained by covalently grafting the nano-carbon material and the metal phthalocyanine.
[0020] The present application also provides an organic magnetic composite material prepared by the preparation method or the use of the organic magnetic composite material as a wave absorbing material.
[0021] The present application provides a method for preparing an organic magnetic composite material, which first reacts a nanocarbon material, a biphenyl compound and 4-nitrophthalonitrile, so that the carboxyl or amino group of the nanocarbon material reacts with the hydroxyl group on the biphenyl, and then undergoes a nucleophilic nitro substitution reaction with 4-nitrophthalonitrile to obtain a nanocarbon material / phthalonitrile monomer; then the monomer generates a phthalocyanine small molecule at a high temperature, undergoes self-polymerization, and the magnetic metal ions and the phthalocyanine rings in the phthalocyanine small molecule are organically combined to obtain a phthalocyanine magnetic metal prepolymer, and finally the prepolymer undergoes a cross-linked and cured thermal polymerization reaction to obtain an organic magnetic wave-absorbing composite material. The present application utilizes the above method to covalently graft the nanocarbon material with the metal phthalocyanine, while solving the problems of poor solubility of the metal phthalocyanine and uneven dispersion of the nanocarbon material, so that the obtained organic magnetic composite material has the properties of high temperature resistance, low density, strong absorption, low frequency, high strength and high modulus. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A schematic diagram of the process for preparing the organic magnetic composite material for this application;
[0023] Figure 2 This is a reflection performance curve of the organic magnetic composite material prepared in the examples of the present application. DETAILED DESCRIPTION
[0024] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.
[0025] In view of the problems in the prior art that nanocarbon materials are easy to agglomerate and metal phthalocyanine has low solubility in the nanocarbon material and metal phthalocyanine composite materials, the present application provides a method for preparing an organic magnetic composite material, such as Figure 1 As shown, Figure 1 The present invention is a schematic diagram of a process for preparing an organic magnetic composite material. The method realizes covalent grafting of nano-carbon materials and metal phthalocyanine, thereby solving the problems of uneven dispersion of nano-carbon materials and poor solubility of metal phthalocyanine. More specifically, the method for preparing the organic magnetic composite material described in the present invention comprises the following steps:
[0026] A) reacting a nano-carbon material, a catalyst, a biphenyl compound and 4-nitrophthalonitrile in an organic solvent to obtain a nano-carbon material / phthalonitrile monomer; the biphenyl compound is a biphenyl compound containing a hydroxyl substituent;
[0027] B) reacting the nano-carbon material / phthalonitrile monomer and a magnetic metal salt in a solvent to obtain a magnetic phthalocyanine metal prepolymer;
[0028] C) solidifying the magnetic phthalocyanine metal prepolymer or its composition to obtain an organic magnetic composite material. In the process of preparing the organic magnetic composite material, the present application first prepares a nano-carbon material / phthalonitrile monomer, that is, the nano-carbon material, the catalyst, the biphenyl compound and the 4-nitrophthalonitrile react in an organic solvent. In the above process, in order to fully react and reduce the generation of by-products, the above process is specifically as follows: the nano-carbon material and the biphenyl compound are mixed in an organic solvent, and then 4-nitrophthalonitrile and the catalyst are added to obtain the nano-carbon material / phthalonitrile monomer after the reaction, wherein the organic solvent is selected from a strongly polar organic solvent, more specifically selected from one or more of N-methylpyrrolidone, N-dimethylformamide and dimethyl sulfoxide, the catalyst is selected from anhydrous potassium carbonate, and the biphenyl compound is selected from 4,4'-dihydroxybiphenyl. In the above process, the carboxyl or amino group of the nano-carbon material reacts with the hydroxyl group on the biphenyl to form a phenol salt, which has a high activity. Under the catalysis of anhydrous potassium carbonate, it undergoes a nucleophilic nitro substitution reaction with 4-nitrophthalonitrile, thereby generating a nano-carbon material / phthalonitrile monomer. The nano-carbon material described in the present application can be selected from one or more of carbon nanotubes and graphene oxide with soluble functional groups, and more specifically can be selected from one or more of carboxyl carbon nanotubes, amino carbon nanotubes, hydroxy carbon nanotubes and graphene oxide. The reaction is carried out in a water bath, the temperature of the water bath is 60 to 100°C, and the time is 6 to 9 hours. The mass ratio of the nano-carbon material, 4,4'-dihydroxybiphenyl, 4-nitrophthalonitrile and anhydrous potassium carbonate is 1: (10 to 20): (20 to 40): (5 to 10).
[0029] The present application then reacts the nano-carbon material / phthalonitrile monomer and the magnetic metal salt in a solvent to obtain a magnetic phthalocyanine metal prepolymer; in this process, the solvent is selected from a strong polar solvent, and the magnetic metal salt is selected from one or more of the magnetic salts of iron, cobalt and nickel; in a specific embodiment, the magnetic metal salt is selected from ferric chloride or nickel chloride. In order to fully react, the above reaction is specifically as follows: the nano-carbon material / phthalonitrile monomer and the solvent are mixed and heated to 60-90°C, and then the magnetic metal salt is added, and the reaction is carried out at 160-180°C for 2-8h, and the magnetic phthalocyanine metal prepolymer is obtained after drying. In this process, the nano-carbon material / phthalonitrile monomer generates phthalocyanine small molecules at high temperature, and some small molecules self-polymerize due to the conjugation of the phthalocyanine ring and the benzene ring of the carbon nanotube material, and the magnetic metal ions and the coordination of the phthalocyanine ring in the phthalocyanine small molecules are organically combined to generate phthalocyanine magnetic metal prepolymers. The mass ratio of the nano-carbon material / phthalonitrile monomer and the magnetic metal salt is (10-20):1.
[0030] Finally, the present application heat-presses and solidifies the magnetic phthalocyanine metal prepolymer or its composition to obtain an organic magnetic composite material; in order to further increase the wave absorption performance of the magnetic organic composite material, a wave absorber can also be added at this stage. When the wave absorber is added, the magnetic phthalocyanine metal prepolymer and the wave absorber are placed in a soluble solvent, dried at 60-80°C to obtain a wave absorber-magnetic phthalocyanine metal prepolymer, and then heat-pressed and solidified to obtain an organic magnetic composite material. During the curing process, the excess nano-carbon material / phthalonitrile monomer or phthalocyanine metal prepolymer undergoes a cross-linking and curing thermal polymerization reaction under the action of a metal catalyst or a curing agent, thereby generating an organic magnetic composite material. The wave absorber is selectively added according to the specific performance requirements of the organic magnetic composite material, and can include one or more types of wave absorbers in magnetic loss, electrical loss and dielectric loss. More specifically, it can be selected from one or more of carbonyl iron, ferrite, graphene, carbon nanotubes, polyaniline and polythiophene. The curing specifically includes pre-curing and post-curing performed in sequence, wherein the pre-curing is specifically maintained at 200°C for 2 hours, and then maintained at 250°C for 4 hours, and the post-curing is specifically maintained at 300°C for 4 hours, and then maintained at 350°C for 4 hours. The pre-curing is a polymerization reaction of the prepolymer to obtain a void-free thermosetting phthalocyanine polymer, and the post-curing is to obtain an organic magnetic composite material. If the curing temperature is too low or the time is too short, the thermal polymerization reaction is insufficient and the curing is incomplete. If the curing temperature is too high or the time is too long, the product will be partially pyrolyzed.
[0031] The present application also provides an organic magnetic composite material prepared by the above method, which is obtained by covalently grafting nano-carbon material and metal phthalocyanine.
[0032] The organic magnetic composite material prepared by the method of the present invention can be specifically used as a wave absorbing material.
[0033] The present application adopts a two-step method to directly introduce a carbon-based absorber into a magnetic phthalocyanine metal, which not only solves the problem of poor solubility of metal phthalocyanine, but also solves the problem of uneven dispersion of nano-carbon materials, and prepares a multifunctional organic magnetic-based absorber with excellent properties such as high temperature resistance, low density, strong absorption, low frequency, high strength and high modulus.
[0034] In order to further understand the present invention, the preparation method of the organic magnetic composite material provided by the present invention is described in detail below in conjunction with examples, and the protection scope of the present invention is not limited by the following examples.
[0035] Example 1
[0036] Graphene oxide (GO) and 4,4'-dihydroxybiphenyl were dissolved in N-methylpyrrolidone (NMP), ultrasonicated for 30 min, then 4-nitrophthalonitrile and anhydrous potassium carbonate were added respectively, stirred in a water bath at 80 °C for 8 h, washed with hydrochloric acid and deionized water, and dried at 80 °C to obtain GO / BPh (phthalonitrile monomer) powder;
[0037] GO / BPh was placed in NMP and stirred at 80°C until completely dissolved, and then FeCl2 was added and the temperature was raised to 180°C for reaction for 6 hours. After precipitation with ethanol, the GO / FePc (ferrophthalocyanine) prepolymer was obtained after washing with deionized water and drying.
[0038] GO / FePc and carbonyl iron (CIP) were placed in a mold for hot pressing and curing. The temperature was increased from room temperature to 200°C at a rate of 5°C / min. After being kept warm for 2 hours, the temperature was increased to 250°C at a rate of 5°C / min and kept warm for 4 hours. The temperature was then increased to 300°C and kept warm for 4 hours. Finally, the temperature was increased to 350°C and kept warm for 4 hours. After cooling in the furnace, a thin plate of 300*300*(1~3)mm was obtained, and the reflectivity was tested using E5071C.
[0039] The preparation methods of Examples 2 to 4 and the comparative example are the same as those of Example 1, and the specific differences are shown in Table 1. The reflectivity performance of the examples is tested, and the results are shown in Tables 2 and Figure 2 As shown;
[0040] Table 1 Example Verification Ratio Related Parameters Data Table
[0041]
[0042] Table 2 Comparative data of reflectivity performance of organic magnetic composite materials prepared in Examples and Comparative Examples
[0043]
[0044] The experimental results show that the organic magnetic composite material prepared in the present application can withstand high temperatures of 300°C to 400°C.
[0045] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0046] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing an organic magnetic composite material, comprising the following steps: A) reacting a nano-carbon material, a catalyst, a biphenyl compound and 4-nitrophthalonitrile in an organic solvent to obtain a nano-carbon material / phthalonitrile monomer; the biphenyl compound is a biphenyl compound containing a hydroxyl substituent; B) reacting the nano-carbon material / phthalonitrile monomer and a magnetic metal salt in a solvent to obtain a magnetic phthalocyanine metal prepolymer; C) curing the magnetic phthalocyanine metal prepolymer or its composition to obtain an organic magnetic composite material.
2. The preparation method according to claim 1, characterized in that: The biphenyl compound is 4,4'-dihydroxybiphenyl, the nano-carbon material is one or more of carbon nanotubes with soluble functional groups and graphene oxide; the magnetic metal salt is one or more of magnetic salts of iron, cobalt and nickel.
3. The preparation method according to claim 2, characterized in that: Step A) is specifically: The nano-carbon material and 4,4'-dihydroxybiphenyl are reacted in a strong polar organic solvent, and then 4-nitrophthalonitrile and anhydrous potassium carbonate are added to obtain a nano-carbon material / phthalonitrile monomer after the reaction.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the nano-carbon material, 4,4'-dihydroxybiphenyl, 4-nitrophthalonitrile and anhydrous potassium carbonate is 1:(10-20):(20-40):(5-10).
5. The preparation method according to claim 1, characterized in that: The mass ratio of the nano-carbon material / phthalonitrile monomer and the magnetic metal salt is (10-20):
1.
6. The preparation method according to claim 1, characterized in that: The curing includes pre-curing and post-curing performed in sequence; the pre-curing is specifically maintained at 200° C. for 2 hours and then maintained at 250° C. for 4 hours, and the post-curing is specifically maintained at 300° C. for 4 hours and then maintained at 350° C. for 4 hours.
7. The preparation method according to claim 1, characterized in that: Step B) is specifically: The nano-carbon material / phthalonitrile monomer is mixed with a strong polar solvent, heated and then a magnetic metal salt is added, and the mixture is dried after reaction to obtain a magnetic phthalocyanine metal prepolymer.
8. The preparation method according to claim 7, characterized in that: The heating temperature is 60-90°C, the reaction temperature is 160-180°C, the reaction time is 2-8 hours, and the drying temperature is 60-80°C.
9. The organic magnetic composite material prepared by the preparation method according to any one of claims 1 to 8 is obtained by covalently grafting nano-carbon material and metal phthalocyanine.
10. Use of the organic magnetic composite material prepared by the preparation method according to any one of claims 1 to 8 or the organic magnetic composite material according to claim 9 as a wave absorbing material.